2D Core/Shell‐Structured Mesoporous Silicene@Silica for Targeted and Synergistic NIR‐II‐Induced Photothermal Ablation and Hypoxia‐Activated Chemotherapy of Tumors. (9th April 2021) - Yin, Haohao; Zhou, Bangguo; Zhao, Chongke; Sun, Liping; Yue, Wenwen; Li, Xiaolong; Li, Hongyan; Li, Shaoyue; Xu, Huixiong; Chen, Yu
Abstract: Silicene nanosheets, the emerging 2D nanomaterial, as the third topology of silicon‐composed materials with distinct physicochemical properties, is a desirable candidate for photothermal‐conversion nanoagent (PTA) and drug‐delivery nanosystems. Inspired by the individual physiochemical properties and structure features of mesoporous silica and 2D silicene, a distinctive 2D core/shell‐structured multifunctional silicon‐composed theranostic nanoplatform (Silicene@Silica) is constructed by coating a mesoporous silica layer onto the surface of 2D silicene nanosheets. The well‐defined mesopores originating from mesoporous silica shell provide the reservoirs for guest drug molecules and the core of silicene produces heat shock upon NIR‐II laser irradiation, aiming to induce the synergistic cancer‐therapeutic modality. Importantly, when AQ4N, hypoxia‐activated prodrug, is introduced into this system, this nanoplatform (Silicene@Silica–AQ4N) exhibits tumor microenvironment (TME)‐responsive and synergistic hyperthermia‐augmented therapeutic bioactivity. Such a nanoplatform can amplify the hypoxia of TME by destroying the tumor microcirculation and then further efficiently activate AQ4N, a DNA affinity agent and topoisomerase II inhibitor. The results reveal that this multifunctional theranostic nanoplatform can efficiently eliminate tumors without recurrence. Abstract : A 2D mesoporous core/shell‐structured multifunctional theranostic nanoplatform (Silicene@Silica–AQ4N) is constructed for targeted and synergistic NIR‐II‐induced photothermal ablation and hypoxia‐activated chemotherapy of tumors. The "core" (silicene) 2D nanoplatform achieves photothermal transformation, which further amplifies the hypoxia of the tumor microenvironment by destroying the tumor microcirculation and then further efficiently activating AQ4N in the "shell" (mesoporous silica) to achieve efficient hypoxia‐activated chemotherapy.